Turkey and the European Union: Processes of Europeanisation - (:unkn) unknown (Ashgate Publishing Ltd, 2012)
The accession of Turkey to the EU presents a fascinating case study for all those with an interest in europeanisation. Officially recognised as a candidate for full membership in 1999 Turkey's negotiations with the EU have been protracted and highly controversial. Turkey and the European Union: Processes of Europeanisation offers a coherent and focussed account of Turkey's recent relations and accession negotiations with the EU. Europeanisation as an explanatory tool is used to review how the EU has successfully induced change in Turkish policies and institutions whilst careful analysis is also conducted into where europeanisation has failed and explores how it may even have inadvertently contributed to forming a backlash against accession. Authoritative local and International contributors provide in-depth analysis as to why the process has had such a varied impact across a range of policies and institutions and ask, given the high costs of joining the EU and decreasing incentives, if europeanisation can still exert an influence in the future. Despite Turkey's unique geographical and political position between East and West the relationship with the EU is not a case sui generis. This book offers valuable insights on the effectiveness of europeanisation for all those within and without the framework of the European Union. © Çiǧdem Nas, Yonca Özer and the contributors 2012. All rights reserved.